Professionalism of Islamic Religious Education Teachers in Strengthening Students’ Religious Character and Soft Skills at MTs Darussalam Sumedang Sari - Siti Umi Latifah; Novita Budiarti (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the professionalism of Islamic Religious Education (PAI) teachers in shaping the religious environment of madrasahs and strengthening students' character. The research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation, and analyzed through data condensation, data presentation, and conclusion drawing. The results of the study show that PAI teachers' professionalism is evident in discipline, example, consistency in guiding religious activities, and active involvement in building the madrasah's religious culture. Religious programs such as Qur'an tadarus, congregational prayers, and Friday alms are effective habituation media in instilling religious values, discipline, responsibility, empathy, and social concern in students. Madrasah policy support, parental involvement, and teacher motivation are supporting factors, while limited facilities, administrative burden, and uneven student discipline are inhibiting factors. This study confirms that the professionalism of PAI teachers is not only about teaching, but also about guiding, setting an example, and sustainably advancing religious culture. Thus, the formation of students' religious character requires synergy between teachers, madrasas, families, and a consistent religious culture.